Why Da'wah - Deedat, Ahmed ([Kuala Lumpur] : Saba Islamic Media, 2008)
Sheikh Ahmed Deedat talk on Da'wah in Islam
Title from title screen
Lecturer : Sheikh Ahmad Deedat
DVD format
Keywords: Da'wah (Islam); Islam -- Missions